Solar insolation in springtime influences age of onset of bipolar I disorder. (19th July 2017) - Bauer, M.; Glenn, T.; Alda, M.; Aleksandrovich, M. A.; Andreassen, O. A.; Angelopoulos, E.; Ardau, R.; Ayhan, Y.; Baethge, C.; Bharathram, S. R.; Bauer, R.; Baune, B. T.; et al.
Abstract : Objective: To confirm prior findings that the larger the maximum monthly increase in solar insolation in springtime, the younger the age of onset of bipolar disorder. Method: Data were collected from 5536 patients at 50 sites in 32 countries on six continents. Onset occurred at 456 locations in 57 countries. Variables included solar insolation, birth‐cohort, family history, polarity of first episode and country physician density. Results: There was a significant, inverse association between the maximum monthly increase in solar insolation at the onset location, and the age of onset. This effect was reduced in those without a family history of mood disorders and with a first episode of mania rather than depression. The maximum monthly increase occurred in springtime. The youngest birth‐cohort had the youngest age of onset. All prior relationships were confirmed using both the entire sample, and only the youngest birth‐cohort (all estimated coefficients P < 0.001). Conclusion: A large increase in springtime solar insolation may impact the onset of bipolar disorder, especially with a family history of mood disorders. Recent societal changes that affect light exposure (LED lighting, mobile devices backlit with LEDs) may influence adaptability to a springtime circadian challenge.